Analisis Pengendalian Kualitas Proses Bonding Garmen Menggunakan Metode Six Sigma Pada PT. PB - Siregar, Rendi Robintang; Sumiati (Faculty of Engineering, Universitas Serambi Mekkah, 2025)
PT PB, one of Indonesia's garment factories, has found defective garments in its production process. These defects result in financial and time losses for the company. This study aims to reduce the defect rate of garment products, analyse the causes of production defects and propose quality control improvements. The Six Sigma method based on the DMAIC approach (Define, Measure, Analyze, Improve, Control) was used in this research. The results showed a Sigma level of 3.48 and a DPMO value of 23,440 defects per million garment productions in October 2024. In addition, five types of garment defects were identified, with the Pareto chart indicating that peel-off accounted for the highest percentage at 29%. Recommendations for improvement include implementing predictive maintenance and evaluating unplanned breakdowns after maintenance, conducting initial inspections and monitoring processes to ensure machines comply with SOPs, strict inspection of fabrics and accessories from receipt to processing, continuous improvement, strict product quality monitoring by operators at each workstation, and increased employee training before machines are operated.